‘Devotio’ Lindsay: Devotional Practices and Visual Culture on the Internet in the 21st Century - Azamar García, Ángel (Eikón / Imago, 2021)
Studies about the theory of religious image and visual pragmatics consider that nowadays the practice of "image-assisted devotion" has fallen into disuse and, therefore, images for affective purposes between human beings and deities are no longer in use. As the Internet is considered the new space where cultural dynamics are created, this article traces within the Lindsay Lohan’s Last Fan web performance (2012-2014) if these visual needs have been extinguished. Using as an analytical tool the procedure of image-assisted meditation: –contemplation, edification, empathy, and imitation– similarities are discovered regarding the devotional process. The search for contact with ineffable entities persists but with different images, referents, genres, and ideologies.